PELATIHAN PEMBUATAN ALAT PERAGA MOTOR LISTRIK DAN PEMBANGKIT LISTRIK TENAGA SURYA SEDERHANA DI SMA YADIKA 8 BEKASI - Malau, Nya Daniaty; Faradiba, Faradiba; Masta, Ngia; Guswantoro, Taat; Sianturi, Manogari; Lumbantobing, Septina Severina; Laia, Setiana; Manullang, Nathasya Grisella; Lase, Fan Damai Sejahtera (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2024)
The development of learning activities in schools is quite important, considering the demands of the 4.0 industrial revolution, which compels students to be more creative in their learning. However, sometimes technology can also be applied in education using simple materials. A Community Service (PkM) activity was conducted at SMA Yadika 8 Bekasi, West Java. The activity took place on May 27, 2024, from 09:00 AM to 12:00 PM WIB. The participants in this PkM program were students from SMA Yadika 8 Bekasi, totaling 120 students, consisting of 88 students from grade X and 32 students from grade XI. The PkM at SMA Yadika 8 Bekasi was divided into two teams: the Electric Motor Teaching Aids Team and the Simple Solar Power Plant Teaching Aids Team. The students were very enthusiastic about the demonstrations and took turns observing the teaching aids being showcased. Additionally, they asked questions about how the teaching aids were made and how they functioned. Based on the satisfaction analysis from 17 statements provided, the results indicate that students' satisfaction with the PkM implementation falls into the good category. Participants' responses were categorized into four areas: response to teaching aids, response to training materials, response to training instructors, and the training process. All four areas received good ratings, indicating that the partners were satisfied with the activities conducted by the PkM Team.